Reimagining Religiously Segregated Spaces: Building Interfaith Sites Through Participatory Photography. (October 2020) - Bhatia, Kiran V.; Pathak-Shelat, Manisha
This article discusses the findings of a participatory photography project that was conceptualized to help Hindu and Muslim students reimagine the religiously marked public spaces they inhabit in their villages. This study is a part of a 2-year long ethnographic project undertaken by the researchers to codesign, with 180 students, critical media literacy curriculum to counter religious discrimination among adolescents in three villages of the Sanand tehsil of Ahmedabad district in Gujarat. In this study, we argue that the configuration of public sites and residential complexes which use religious identities as a categorical imperative reinforce the communal divide in interfaith societies. It is, thus, crucial to create a site for interfaith engagements where young individuals can collectively participate to make sense of the spaces they inhabit and in this participation change the normalized code of conduct. In this article, we concede that participatory photography provides an avenue through which the young student-participants can find ways to communicate with the "religious other" and insert public imagination with new meanings related to the physical sites they frequent.